Pengaruh Equilibrium Kandungan Air Batubara Halus Terhadap Nilai Kalor Bakar Batubara Halus (Fine Coal) - Mawardi Anwar; Hary Sanjaya; Meyci Trisna (Departemen Kimia FMIPA UNP, 2013)
The increasing of requirement of domestic cement for a number of years will affect directly to usage of coal as especial fuel for cement production. So that Important to know the usage condition of coal yielding coal with superordinate calorivic value, with better economic value, and smaller negative impact to environment, where with slimmer usage amount of coal better yield coal with higher calorivic value because more and more amount of used coal also will improve the waste that able to influence environment. Have been researched water equilibrium of fine coal with aim to lessen the amount of fine coal usage for cement production process, because from data result of research got calorivic value which mounting of fine coal after done equilibrium of water content in fine coal. Fine coal sample before and after obstetrical equilibrium of its water is determined change of that calorivic value (Cal/g) use Bomb Calorimeter PARR 1261, content of water (%) use Moisture Analyzer, content of sulphur (%), and its dusty content. Result of which is got that after water equilibrium happened minimizing the mass of fine coal’s sample, after done the determination of water content happened minimizing of water content that is equal to 3.14% or happened minimizing that equal to 17% from water content before equilibrium. While for the calorivic value increase until 189 Cal/g or happened increase equal to 3% from calorivic value of sample before equilibrium, for sulphur and dusty content happened increase successively equal to 7% and 5% from content of sample before equilibrium.